Infants of Diabetic Mothers and Associated Complications in Neonatal Intensive Care Unit in Misurata Center - Moktar Assadi; Salima Alburki; Abdulaleem Assadi; Ali Rajab; Faraj Gadora (AlQalam Journal of Medical and Applied Sciences, 2024)
Infants of diabetic mothers (IDM) are at an increased risk of various complications. The aim of this study is to evaluate the prevalence, demographic and clinical characters of IDM admissions to the neonatal intensive care unit, and the factors associated with morbidity and mortality. The study is a 1-year retrospective observational study involving all the cases of IDM admitted to the neonatal intensive care unit at Misurata. The study examined the association of the following ante- peri- and postnatal factors to the morbidity and mortality rate of IDM. A total of 103 IDM were admitted to the NICU with mother age range of 31- 35 years. About 84% of the mothers had multiple pregnancies, 81.5% of the IDM were born through C-section. 72% of the mothers had gestational diabetes. 59% of IDMs were females. Median gestational age was 36 – 38 weeks which was associated with higher mortality rate (p = 0.041) ,40% of them were post term. Macrosomia was the most common complication; 41%. About 22% had hypocalcemia and 12% had RDS. Six cases had congenital heart disease (CHD). About 26% of the cases required intravenous fluid (IVF) which had a significantly higher mortality rate (25% vs. 1.3%) (p = 0.008). IDM are at a higher risk of congenital and acquired morbidities and mortality. Delayed birth and the mode of delivery (elective or urgent C-section) are associated with the severity of the gestational diabetes which is significantly associated with higher mortality rate. الأطفال حديثي الولادة لأمهات مصابات بالسكري معرضون لخطر متزايد للإصابة بمضاعفات مختلفة. يهدف هذا البحث إلى تقييم معدل الانتشار والخصائص الديموغرافية والكلينيكية لقبول حديثي الولادة لأمهات مصابات بالسكري في وحدة العناية المركزة لحديثي الولادة والعوامل المرتبطة بالمرض والوفيات. هذه دراسة استرجاعية لمدة عام تشمل جميع حالات حديثي الولادة لأمهات مصابات بالسكري المقبولة في وحدة العناية المركزة لحديثي الولادة في مصراتة. بفحص الدراسة العلاقة بين ما يلي:العوامل ما قبل والولادة وبعد الولادة معدل المراض والوفيات لدى حديثي الولادة لأمهات مصابات بالسكري. خلال فترة الدراسة، تم إدخال 103 حديثي الولادة لأمهات مصابات بالسكري إلى وحدة العناية المركزة لحديثي الولادة تتراوح أعمار أمهاتهن بين 31 و 35 عامًا. حوالي 84٪ من الأمهات لديهن حالات حمل متعددة ، و 81.5٪ من حديثي الولادة لأمهات مصابات بالسكري ولدن من خلال عملية قيصرية. 72٪ من الأمهات مصابات بسكري الحمل. 59٪ من حديثي الولادة لأمهات مصابات بالسكري من الإناث. متوسط عمر الحمل ’36 - 38’ أسبوعًا والذي ارتبط بمعدل وفيات أعلى (ص = 0.041). 40٪ منهم ولدوا بعد الموعد. تضخم المشيمة هو أكثر المضاعفات شيوعًا لهذه الحالة بنسبة 41٪. 22٪ يعانون من نقص كالسيوم الدم و 12٪ يعانون من متلازمة الضائقة التنفسية لدى حديثي الولادة. 6 حالات مصابة بعيوب خلقية بالقلب. 26٪ من الحالات احتاجت إلى استبدال السوائل الوريدية والذي كان له معدل وفيات أعلى بكثير (25٪ مقابل 1.3٪) (ص = 0.008). الأطفال حديثي الولادة لأمهات مصابات بالسكري معرضون لخطر أكبر للإصابة بأمراض ومضاعفات خلقية ومكتسبة والوفيات. يرتبط تأخر الولادة وطريقة الولادة (عملية قيصرية اختيارية أو طارئة) بشدة سكري الحمل الذي يرتبط ارتباطًا وثيقًا بمعدل وفيات أعلى